Peran Promosi dan Kualitas Layanan dalam Membentuk Loyalitas Pelanggan: Efek Mediasi Kepuasan Pelanggan dalam Industri Jasa - Kambuaya, Balthazar; Rante, Yohanes (Jurnal Bisnis dan Kewirausahaan, 2026)
The increasing competition in Indonesia’s Islamic banking sector requires Islamic Rural Banks (Bank Pembiayaan Rakyat Syariah/BPRS) to strengthen long-term customer relationships. Customer loyalty has become a strategic asset that determines sustainability, particularly for regional Islamic banks such as BPRS ABC. This study examines the role of promotion and service quality in shaping customer loyalty, with customer satisfaction as a mediating variable. Using a quantitative approach, data were collected from 100 customers of BPRS ABC and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that promotion and service quality significantly influence customer satisfaction and customer loyalty. Furthermore, customer satisfaction significantly mediates the relationship between promotion, service quality, and loyalty. The study highlights the importance of integrating effective promotional strategies and superior service quality to enhance satisfaction and foster sustainable loyalty in Islamic rural banking institutions.